1977
DOI: 10.1246/bcsj.50.710
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism of 4-Pyridones

Abstract: The tautomeric constants, Kt, of several 4-pyridones were determined by measurement of pKa values. For 2-substituted 5-methoxy-4-pyridones, the Kt values were correlated to the substituent constants σ, the equation logkt=2.98+2.93σm−6.18σo being obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The extremely low solubilities shown by the antimalarial 4­(1 H )-pyridones in aqueous media had been attributed not only to their relatively high lipophilicities but also to the intrinsic structural features of the 4­(1 H )-pyridone rings, in particular their marked tendency to form strong hydrogen-bonding networks. In this way, it had been reported in the literature that clopidol and other 4­(1 H )-pyridones predominantly adopted their 4-keto tautomer forms in the solid state, forming structures supported by strong hydrogen-bonding networks. This is in accordance with the high melting points (mp > 250 °C) measured for some of the 4­(1 H )-pyridones synthesized (data not reported here).…”
Section: Resultsmentioning
confidence: 73%
“…The extremely low solubilities shown by the antimalarial 4­(1 H )-pyridones in aqueous media had been attributed not only to their relatively high lipophilicities but also to the intrinsic structural features of the 4­(1 H )-pyridone rings, in particular their marked tendency to form strong hydrogen-bonding networks. In this way, it had been reported in the literature that clopidol and other 4­(1 H )-pyridones predominantly adopted their 4-keto tautomer forms in the solid state, forming structures supported by strong hydrogen-bonding networks. This is in accordance with the high melting points (mp > 250 °C) measured for some of the 4­(1 H )-pyridones synthesized (data not reported here).…”
Section: Resultsmentioning
confidence: 73%
“…It was demonstrated that K T depends linearly on the Hammett s-constant of the substituent. 79 It was also found that the electrondonating and electron-withdrawing substituents led to increases and decreases in logK T , respectively.…”
Section: Tautomerism In Pyridinesmentioning
confidence: 97%
“…Previously, we reported the tautomeric ratio of some 4-pyridones by measurement of dissociation constants of their N-methylated and 0-methylated compounds [4]. The present communication deals with the synthesis of 6-arylazo-5-hydroxy-2-hydroxymethyl-4-pyridones and their N-methylated and 0-methylated compounds, which are N-analogous to 6-arylazo-substituted kojic acids.…”
mentioning
confidence: 88%
“…

5-Hydroxy-2-hydroxymethyl-4-pyridone (1) and 5-hydroxy-2-hydroxymethyl-1-methyl-4-pyridone (2) reacted with arenediazonium salts to give 6-arylazo-substituted compounds 3a-d and 4a-d, respectively. The latter exists as its hydrate, which shows a tautomeric phenylhydrazono structure, and was not methylated with diazomethane.Previously, we reported the tautomeric ratio of some 4-pyridones by measurement of dissociation constants of their N-methylated and 0-methylated compounds [4]. Heterocyclic Chem., 23, 333 (1986).

Since kojic acid is an attractive material as a chemically and biologically important substance, many of its reactions have been carried out.

…”
mentioning
confidence: 99%